Characteristics of patients making serious inhaler errors with a dry powder inhaler and association with asthma-related events in a primary care setting. (15th March 2016) - Westerik, Janine A. M.; Carter, Victoria; Chrystyn, Henry; Burden, Anne; Thompson, Samantha L.; Ryan, Dermot; Gruffydd-Jones, Kevin; Haughney, John; Roche, Nicolas; Lavorini, Federico; Papi, Alberto; Infantino, Antonio; et al.
Abstract: Objective : Correct inhaler technique is central to effective delivery of asthma therapy. The study aim was to identify factors associated with serious inhaler technique errors and their prevalence among primary care patients with asthma using the Diskus dry powder inhaler (DPI). Methods : This was a historical, multinational, cross-sectional study (2011–2013) using the iHARP database, an international initiative that includes patient- and healthcare provider-reported questionnaires from eight countries. Patients with asthma were observed for serious inhaler errors by trained healthcare providers as predefined by the iHARP steering committee. Multivariable logistic regression, stepwise reduced, was used to identify clinical characteristics and asthma-related outcomes associated with ≥1 serious errors. Results : Of 3681 patients with asthma, 623 (17%) were using a Diskus (mean [SD] age, 51 [14]; 61% women). A total of 341 (55%) patients made ≥1 serious errors. The most common errors were the failure to exhale before inhalation, insufficient breath-hold at the end of inhalation, and inhalation that was not forceful from the start. Factors significantly associated with ≥1 serious errors included asthma-related hospitalization the previous year (odds ratio [OR] 2.07; 95% confidence interval [CI], 1.26–3.40); obesity (OR 1.75; 1.17–2.63); poor asthma control the previous 4 weeks (OR 1.57; 1.04–2.36); female sex (OR 1.51; 1.08–2.10); and no inhaler technique review during the previous year (OR 1.45; 1.04–2.02). Conclusions : Patients with evidence of poor asthma control should be targeted for a review of their inhaler technique even when using a device thought to have a low error rate.